1980
DOI: 10.1002/1097-0142(19800515)45:10<2439::aid-cncr2820451003>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease: Unfolding concepts concerning its nature, management and prognosis

Abstract: The evolution of our concepts concerning the fundamental nature and natural history of Hodgkin's disease is reviewed. Recent evidence establishes that it is indeed a malignant neoplasm, albeit a curious one, the giant cells of which display aneuploid karyotypes, often with marker chromosomes indicating their clonal derivation, and the functional and surface marker properties of cells of the mononuclear phagocyte series. The disease tends initially to spread by contiguity from one lymph node chain to others wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
17

Year Published

1981
1981
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(47 citation statements)
references
References 150 publications
1
29
0
17
Order By: Relevance
“…As a result of modern therapeutic advances histologic subtype has in many studies in recent years shown a diminishing influence on prognosis in the sense that the difference in prognosis between NS and MC has been virtually eliminated in early stage disease (Kaplan, 1980a). In the present study histologic subtype is a significant prognostic factor with LP having the best and MC the poorest disease free survival.…”
Section: Resultssupporting
confidence: 49%
“…As a result of modern therapeutic advances histologic subtype has in many studies in recent years shown a diminishing influence on prognosis in the sense that the difference in prognosis between NS and MC has been virtually eliminated in early stage disease (Kaplan, 1980a). In the present study histologic subtype is a significant prognostic factor with LP having the best and MC the poorest disease free survival.…”
Section: Resultssupporting
confidence: 49%
“…THE CURRENT REGIMENS of therapy for and impaired host defences against certain HD have produced a major decrease in the infections (Goffinett et al, 1972; Weitzman overall death rate, with long-term relapse-& Aisenberg, 1977; Askergren & Bjorkfree survival and cure in the vast majority holm, 1980) have been noted. By better of young (< 45 years) patients with early-identification of "good prognosis" patients stage disease (Kaplan, 1980a). However, one might be able to reduce the total some young and many elderly patients do amount of radio-and chemotherapy withnot enter complete remission, or relapse out losing the therapeutic effectiveness.…”
mentioning
confidence: 99%
“…Biological tests such as the bilirubin concentration, BSP retention, gammaglutamyl transpeptidase, oxaloacetic or glutamatepyruvate transaminases, or 5-nucleotidase (which is useful in the case of malignant lymphomas) are not commonly employed (Belliveau et al, 1974;Deeble & Goldberg, 1980). Alkaline phosphatases appear more useful: numerous studies have shown a clear correlation between the AP concentration and the disease stage (Belliveau et al, 1979;Deeble & Goldberg, 1980;Aisenberg et al, 1970;Kaplan, 1980), whether or not there is any histologically proven liver involvement. The actual significance of elevation of AP levels remains unclear: an unexplained and occasionally intense liver retention syndrome has been observed for some time, disappearing in some cases after supradiaphragmatic radiotherapy of stage I or II disease (Perera et al, 1974).…”
Section: Discussionmentioning
confidence: 99%